2020
DOI: 10.1371/journal.pone.0241383
|View full text |Cite
|
Sign up to set email alerts
|

Likes and impulsivity: Investigating the relationship between actual smartphone use and delay discounting

Abstract: The omnipresence of smartphones among adolescents and adults gives rise to the questions about excessive use and personality factors which are associated with heavier engagement with these devices. Previous studies have found behavioral similarities between smartphone use and maladaptive behaviors (e.g. drinking, gambling, drug abuse) in the context of intertemporal choice but mostly relied on participants’ self-reports regarding engagement with their phone. In this study, we collected actual usage data by sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
1
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
0
15
1
5
Order By: Relevance
“…When the traditional telephone was a fixed device in the home or office, there was a degree of freedom that has been lost since smartphones have become almost omnipresent [79]. The use of mobile phones has caused people to be able to be localized anytime and everywhere via various communication apps and social networks, which has led to a feeling of urgency to respond, even at the expense of interrupting work and academic and/or social life, which can lead to a high level of communication overload [80,81]. This has increased during the COVID-19 pandemic because social isolation has increased the need for virtual communication [56].…”
Section: Discussionmentioning
confidence: 99%
“…When the traditional telephone was a fixed device in the home or office, there was a degree of freedom that has been lost since smartphones have become almost omnipresent [79]. The use of mobile phones has caused people to be able to be localized anytime and everywhere via various communication apps and social networks, which has led to a feeling of urgency to respond, even at the expense of interrupting work and academic and/or social life, which can lead to a high level of communication overload [80,81]. This has increased during the COVID-19 pandemic because social isolation has increased the need for virtual communication [56].…”
Section: Discussionmentioning
confidence: 99%
“…The present data suggest that children’s ability to control thoughts and emotions is the mechanism underlying the association between delay discounting and addictive use and thus is a superior predictor of problematic behavior towards digital devices. Existing studies focusing on smartphone use and delay discounting found mixed results on a mediating role of self-control (mediation see Wilmer & Chein [ 45 ], no mediation see Schulz van Endert & Mohr [ 24 ]). Due to the cross-sectional and observational nature of the data, no conclusion with regard to mediation can be made in this present study [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…parents, teachers or peers) or even actual screen time data, as shown in e.g. Schulz van Endert & Mohr [ 24 ]. Third, due its novelty the DASC has not yet undergone extensive validation yet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, recent studies have found an association between screen time, i.e., time spent with a smartphone, laptop or tablet, and delay discounting (Wilmer and Chein, 2016;Schulz van Endert and Mohr, 2020). While the direction of causality is unknown, people who spend more time with digital devices tend to choose more impulsively in delay discounting tasks with monetary rewards.…”
Section: Introductionmentioning
confidence: 97%